Diagnóstico y tratamiento del síndrome de hellp en embarazo de 39 semanas. - Vera Troya, Miguel Angel (2020)
HELLP syndrome is considered one of the main complications that occur with preeclampsia-eclampsia, however, it also occurs without hypertensive disease of pregnancy, this syndrome is characterized by microvascular endothelial damage, however, its pathophysiology is not yet well defined , it can occur in pregnancy or the puerperium, it is characterized by hemolysis, increased liver enzymes and plaquetopenia and its relevance lies in the fact that it is associated with the appearance of serious perinatal complications and increased maternal mortality. There is evidence of a case of a female patient with a 39-week pregnancy who goes to the hospital to be evaluated by the gyneco-obstetric emergency area where she presents a clinical picture characterized by holocranial headache, which is accompanied by photopsy, epigastric pain, increased blood pressure alterations in the toxemic profile where the respective management is given after the pregnancy by cesarean section, subsequently patient is discharged in good condition.